Varieties of residential capitalism in Turkey - ARSLAN TAÇ, ZEYNEP (Routledge, London/New York, 2022)
Economic, demographic, political, and spatial factors shape the housing system. The housing system of Turkey is mostly shaped by informality and financialization of housing (FoH) that the construction sector in general, housing and real estate sector, in particular, are central to capital accumulation, wealth creation, and national economic growth. As a late-stage capitalist country, Turkey\"s dependent market economy is increasingly integrated into the global system; besides, due to the changing role of the State from a regulator to an active financial market actor Turkey has been experiencing state-led financialization in the housing market. This chapter explores the interconnection between macroeconomics, finance, and housing concerning historical factors and dynamics in the development of the FoH in Turkey. The chapter concludes that the characteristics of FoH in Turkey; reveal highly developed Real estate Investment Trusts (REITs), relatively new mortgage system and low mortgage-GDP rate, huge informal housing stock with high potential rent, and the State\"s direct intervention in the housing market, which set an example to the variegated structure of FoH in the Global South.
Keywords: Sosyal ve Beşeri Bilimler; Coğrafya; İktisadi Coğrafya; Siyaset Bilimi; Kamu Yönetimi; Kentleşme ve Çevre Sorunları; Mimarlık; Şehir ve Bölge Planlama; Diğer; Mühendislik ve Teknoloji; Social Sciences and Humanities; Geography; Economic Geography; Political Science; Public Administration; Urbanization and Environmental Problems; Architecture; City and Regional Planning; Other; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Yerbilimleri; Sanat ve Beşeri Bilimler; Sosyal Bilimler Genel; COĞRAFYA; MİMARİ; SİYASET BİLİMİ; KAMU YÖNETİMİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); Arts & Humanities (AHCI); Social Sciences (SOC); GEOSCIENCES; ARTS & HUMANITIES; SOCIAL SCIENCES, GENERAL; GEOGRAPHY; ARCHITECTURE; POLITICAL SCIENCE; PUBLIC ADMINISTRATION; Siyasi bilimler ve Uluslararası İlişkiler; Coğrafya, Planlama ve Geliştirme; Mimari; Sosyal Bilimler ve Beşeri Bilimler; Fizik Bilimleri; Political Science and International Relations; Geography, Planning and Development; Social Sciences & Humanities; Physical Sciences